Longitudinal changes in choroidal thickness and choroidal vascularity index in age-related macular degeneration - Vidal Oliver, Lourdes; Spissinger, Sabrina; Herzig de Almeida, Elisa; Garzone, Davide; Finger, Robert P. (Ophthalmic research, 2024)
Introduction: The aim of the study was to investigate the rate of choroidal thinning and Choroidal Vascularity Index (CVI) changes over time in eyes with different stages of age-related macular degeneration (AMD) and control eyes. Methods: Retrospective longitudinal study of 105 eyes with different stages of AMD: non-advanced (n = 46), exudative (n = 28), central complete retinal pigment epithelium and outer retinal atrophy (cRORA) (n = 5) and healthy eyes (n = 26). We evaluated choroidal thickness (CT) and CVI at baseline and during 2-4 years of follow-up. After adjustment for age and sex, we estimated the rate of change per year of CT and CVI in each group. We also performed logistic regression to analyze the relationship between baseline CT and CVI with AMD progression. Results: The mean age of the included patients was 77.1 years with a mean follow-up of 3.36 years. Healthy eyes had higher baseline CT and CVI values compared to eyes with AMD. Exudative AMD showed a significant annual decrease in subfoveal CT (−5.1% per year vs. −3.5% in controls) and in the temporal and nasal sectors (−5.3% and −6.3%). CVI decreased during follow-up in all study groups, most in eyes with central cRORA (−1.09% per year). Conclusion: CVI and CT values are reduced in eyes with AMD compared to healthy eyes. Eyes with exudative AMD have the highest annual rate of choroidal thinning, while CVI decreases most in eyes with central cRORA. CT and CVI may aid in a further stratification of AMD progression risk.